Preliminary Findings of a Ten-Item Scale to Assess the Commitment of Low-Income Owners to Their Companion Animals. (2nd January 2021) - Rauktis, Mary E.; Hoy-Gerlach, Janet; Sewall, Craig J. R.; Lee, Hyunji; Bickel, Laura
ABSTRACT: While there is a substantive body of research on benefits conveyed via the human–animal bond (HAB), less is understood about disruptions to HAB and how to potentially prevent such. The construct of commitment can elucidate such scenarios and may also help inform related interventions; however, there are few empirical measures of commitment to a companion animal, and none specific to low-income owners. The Commitment to Pets measure was created to address this gap. The scale was included in a mixed methods study of food security administered to 392 low-income adults utilizing food pantries in a Northeastern city in the United States. Of this number, 258 (66%) owned pets. Data collection included a self-administered questionnaire about demographics, food security, health, and wellbeing, and for those with pets, animal attachment, commitment, and animal information. Qualitative interviews were conducted with 15 pet-owning individuals who completed the questionnaire and agreed to be contacted and interviewed over the phone about food security and their pets. Exploratory factor analyses found three underlying factors: financial costs/burdens; pet behaviors and problems; family problems. These subscales associated with attachment in that higher attachment was correlated with greater commitment. However, the value of the correlations suggests they are different constructs. Moreover, analysis of the qualitative interviews supported these underlying constructs and suggested that unexpected financial costs of veterinary care and food was a major factor in considering ongoing pet ownership, even when there was a deep level of attachment between humans and their animals. Commitment is a complex construct, and additional measurement studies are needed. Findings suggest community outreach models using cross–systems collaboration have potential to support low-income pet-owning families in their commitment to pets and may aid in prevention of surrenders and HAB disruptions.